2018
DOI: 10.1016/j.omtn.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The ASH1-miR-375-YWHAZ Signaling Axis Regulates Tumor Properties in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a worldwide malignance, and the underlying mechanisms of this disease are not fully elucidated. In this study, the existence and function of achaete-scute homolog-1 (ASH1)-miR-375-YWHAZ signaling axis in HCC were determined. Our experiments and the Cancer Genome Atlas (TCGA) sequencing data analyses showed that ASH1 and miR-375 were significantly downregulated, whereas YWHAZ was significantly upregulated in HCC. Furthermore, we found that ASH1 positively regulates miR-375, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…Of note, in SMMC-7721 cells, 14-3-3ζ positively regulated the mRNA expression of ATG7 gene. 18 Such findings together with our current data suggest that 14-3-3ζ may F I G U R E 5 14-3-3ζ contributes chemoresistance of HCC cells to CDDP by inducing autophagy. HCC-LM3 and CSQT2 cells were infected with n.c. oe-LV, 14-3-3ζ oe-LV or beclin 1 sh-LV, and 48 h later, cells were treated with 100 μmol/L CDDP, 10 mmol/L 3-MA or 30 μmol/L chloroquine for additional 24 h. (A, C, E,G) The protein levels of phosphobeclin 1 S295 , beclin 1 and LC3 were determined with Western blot analysis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Of note, in SMMC-7721 cells, 14-3-3ζ positively regulated the mRNA expression of ATG7 gene. 18 Such findings together with our current data suggest that 14-3-3ζ may F I G U R E 5 14-3-3ζ contributes chemoresistance of HCC cells to CDDP by inducing autophagy. HCC-LM3 and CSQT2 cells were infected with n.c. oe-LV, 14-3-3ζ oe-LV or beclin 1 sh-LV, and 48 h later, cells were treated with 100 μmol/L CDDP, 10 mmol/L 3-MA or 30 μmol/L chloroquine for additional 24 h. (A, C, E,G) The protein levels of phosphobeclin 1 S295 , beclin 1 and LC3 were determined with Western blot analysis.…”
Section: Discussionsupporting
confidence: 68%
“…Autophagy is precisely orchestrated by multiple autophagy‐related proteins (ATGs) . A study from Zhao et al showed that ATG7 mRNA expression was up‐regulated after 14‐3‐3ζ overexpression and down‐regulated when 14‐3‐3ζ was knocked down in SMMC‐7721 cells. Weerasekara and coworkers proved that, under hypoxia, the phosphorylation of Atg9A at S761 (S, serine) was enhanced by AMPK, which enabled its binding to 14‐3‐3ζ, thereby promoting Atg9A recruitment to LC3‐positive autophagosomes .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Watanabe et al 24 revealed that levels of YWHAZ expression were associated with higher rate of lymph node metastasis, larger tumor size, and poorer Siewert type in patients with adenocarcinoma of the esophagogastric junction. 32 The above result showed that YWHAZ expression was associated with lymph node metastasis and present distant metastasis in NSCLC patients, and several published reports showed YWHAZ played important role in regulating tumor cell metastasis. 25 In prostate cancer patients, high levels of YWHAZ expression were correlated with high Gleason score, PSA relapse and castration-resistant.…”
Section: Discussionmentioning
confidence: 79%
“…In order to elucidate the ceRNA regulatory mechanism, we established a PPI network and obtained 9 hub genes (STAT3, CNOT7 BTG3, E2F1, TRIM37, YWHAZ, RBBP7, KIF23, ESR1). GO functional annotation and KEGG pathway analysis revealed the 9 hub genes were enriched in hepatitis B associated pathways and the important roles of these 9 hub genes in HCC have also been con rmed [37][38][39][40][41][42][43][44][45]. However, the relationship between the 9 hub genes and FBXL19-AS1 has not been reported.…”
Section: Discussionmentioning
confidence: 99%